REKONSILIASI FISKAL TERHADAP LAPORAN KOMERSIAL UNTUK MENGHITUNG PAJAK PENGHASILAN BADAN PADA PT. SINAR AMADA TAHUN 2014 - Sunarmin Sunarmin; Tavitri Rangkuti; Dian Ramadanni (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
PT.Sinar Amada is a company engaged in the field of trade. As a company that will obey the tax, PT. Sinar Amada is obliged to perform the calculation and reporting of income taxes according to the provisions referred to under the taxation laws in force, so that the Trading Company's annual financial reports and make the income statement for reconciliation implemented fiscal. The purpose of this final report is to determine whether to report fiscal reconciliation of profit / loss of commercial PT. Sinar Amada in 2014 in accordance with the Income Tax Act No. 36 Year 2008. And how the rates used by PT. Sinar Amada beam to calculate the corporate income tax. From this study, the authors can conclude that both fiscal reconciliation PT. Amada rays and calculating rates of Corporate Income Taxes in 2014 were carried out by PT. Amada beam in accordance with the Income Tax Act No. 36 in 2008.